SOURCE STUDIES OF CENTRAL ASIA – CHINA RELATIONS (16TH – 21ST CENTURIES) - Keldiyorov Javakhir Bakhtiyor ogli (American Journals Publishing, 2025)
The uniqueness of the historical past of the Central Asian region, the history of relations between the peoples of Central Asia and China, as well as the significance of the processes taking place here for world history, increase the interest of researchers in them. This article analyzes sources related to relations between China and Central Asia.
Keywords: Central Asia and China, historical analysis, economic and social relations, topography of the territories, the level of research of sources.